Lenses on teaching : developing perspectives on classroom life - Chiarelott, Leigh; Davidman, Leonard; Ryan, Kevin (Fort Worth, TX : Harcourt Brace College Publisher, 1998)
An introduction to field experiences for pre-service teachers, this work is a combined workbook and text that student teachers can use to focus their observations in elementary and secondary classrooms.
Includes bibliographical references and indexes.
Keywords: Observation (Educational method); Teaching; Teachers